Combining odours isolated from phylogenetically diverse sources yields a better lure for yellow jackets. Issue 4 (25th June 2015) - Unelius, C Rikard; Suckling, D Maxwell; Brown, Robert L; Jósvai, Julia K; El‐Sayed, Ashraf M
Abstract: BACKGROUND: Invasive wasps have major impacts on bird populations and other biodiversity in New Zealand beech forests, and new solutions are needed for their management. Baits were combined from four phylogenetically diverse sources (protein and carbohydrate) to improve attraction to a level that could be used as the basis for more powerful attract‐and‐kill systems. Many compounds from honey, scale insect honeydew, fermenting brown sugar and green‐lipped mussels were highly attractive and, when combined, outcompeted known attractants. RESULTS: The equivolumetric lure (equal parts of 3‐methylbut‐1‐yl acetate, 2‐ethyl‐1‐butanol, 1‐octen‐3‐ol, 3‐octanone, methyl phenylacetate and heptyl butanoate), gave a 5–10‐fold improvement over the known attractant, octyl butanoate, and other previously patented lures. An economically optimised lure of the same compounds, but in a ratio of 2:1.6:1:1:2:2.4, was equally attractive as the equal‐ratio lure. Pilot mass trapping attempts with this latter lure revealed that >400 wasps trap −1 day −1 could be caught at the peak of the season. CONCLUSION: The new lures are comprised of compounds from animals, plants and fungi, thus targeting the omnivorous behaviour of these wasps. © 2015 Society of Chemical Industry